On Contra $π gγ$-Continuous Functions (Journal of Informatics and Mathematical Sciences, 2014)
In this paper, we introduce and investigate the notion of contra $π gγ$-continuous functions by utilizing $π gγ$-closed sets [31]. We obtain fundamental properties of contra $π gγ$-continuous functions and discuss the relationships between contra $π gγ$-continuity and other related functions.
Keywords: $π gγ$-closed set; $π gγ$-continuous function; contra $π gγ$-continuous function; contra $π gγ$-graph; $π gγ$-normal space